The MS Remyelinating Drug Bexarotene (an RXR Agonist) Promotes Induction of Human Tregs and Suppresses Th17 Differentiation In Vitro - Gaunt, Christopher M.; Rainbow, Daniel B.; Mackenzie, Ruairi J.; Jarvis, Lorna B.; Mousa, Hani S.; Cunniffe, Nicholas; Georgieva, Zoya; Brown, J. William; Coles, Alasdair J.; Jones, Joanne L. (Frontiers in Immunology, 2021)
The retinoid X receptor agonist bexarotene promotes remyelination in patients with multiple sclerosis. Murine studies have also demonstrated that RXR agonists have anti-inflammatory effects by enhancing the ability of all-trans-retinoic acid (atRA) to promote T-regulatory cell (Treg) induction and reduce Th17 differentiation in vitro. By stimulating human naïve CD4 T-cells in the presence of Treg or Th17 skewing cytokines, we show that bexarotene also tips the human Treg/Th17 axis in favour of Treg induction, but unlike murine cells this occurs independently of atRA and retinoic acid receptor signalling. Tregs induced in the presence of bexarotene express canonical markers of T-regulation and are functionally suppressive in vitro. Treg numbers did not increase in the blood of trial patients receiving bexarotene; this is unsurprising as Treg induction is likely to occur within tissues. These findings lend support to developing RXR agonists as treatments of autoimmune diseases, in particular multiple sclerosis.